Immunologic influences of hyperthermia in a rat model of obstructive jaundice - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 2001)
In this study, the effect of hyperthermia on immune response and bacterial translocation from the gut in jaundiced rats was assessed. In hyperthermic (HP; N = 8) and normothermic (NP; N = 8) preconditioning groups, rats were preconditioned by hyperthermia for 15 min at 42 degreesC or 38 degreesC, respectively. After 8 hr, the common bile duct (CBD) of each animal was ligated. In thermal (TT; N = 8) and normothermic treatment groups (NT; N = 8) the CBD of the animals was ligated, and after seven days rats were treated by hyperthermia for 15 min at 42 degreesC and 38 degreesC, respectively. The rats in the preconditioning groups (HP and NP) were killed at day 7 and rats in the treatment groups (TT and NT) were killed 8 hr after they were put in a water bath. Determination of the immunophenotypes of lymphocytes and serum levels of bilirubin was done in serum samples taken just after death. The quantity and identify of translocated bacteria were determined in tissue samples of mesenteric lymph nodes, spleen, and liver. NK cell expression as well as CD4(+)/CD8(+) ratio were elevated in HP group when compared to NP group. CD8(+) expression was found to be low in HP group when compared to NP group. CD4(+), CD11b(+), and B cell expressions were not found to be different between HP and NP groups. All immunologic parameters were similar when TT and NT groups were compared to each other. In the TT group, half of the rats revealed bacterial translocation, whereas in all other groups, we determined translocation in only 1/8 rats. The application of hyperthermia as preconditioning rather than applying it after the establishment of jaundice seemed to be beneficial. Hyperthermic preconditioning led an improvement in immune responses whereas the latter resulted an increase in bacterial translocation with no favorable influence on immune system. Bacterial translocation was unrelated with the immune status.
Keywords: hyperthermia; hyperthermic preconditioning; obstructive jaundice; cellular immunity; bacterial translocation; BACTERIAL TRANSLOCATION; DYSFUNCTION; RESPONSES; BARRIER; SYSTEM; SEPSIS; BETA